PENGARUH TEKNIK PEMBELAJARAN DAN KECERDASAN LINGUISTIK TERHADAP KETERAMPILAN MENULIS TEKS RECOUNT BAHASA INGGRIS - Oktariyani Oktariyani Yani; layni Asra Asra (Wanastra: Jurnal Bahasa dan Sastra, 2018)
ABSTRACT- This research aimed at finding out the effect of learning technique and linguistic intelligence towards recount text writing skill in SMPN 1 Way Tenong West Lampung. The research used a 2x2 factorial design. The sample was 30 students selected from the students of SMPN 2 Way Tenong West Lampung through multistage random sampling. There were two chosen groups as experimental. The first group taught by using Cooperative Integrated reading Composition (CIRC) learning technique and second group taught by Student Team Achievement Division (STAD) learning technique. The results of this research showed that (1) there is a difference score of the recount text writing skills English language learning among groups of students using learning techniques (CIRC) and a group of students who are learning using learning techniques (STAD) (the score of F = 0.99> F 0.258), (2) there is a positive interaction between teaching technique and linguistic intelligence (high and low) on the results of recount text writing skills in English (F value = 25.50> F = 2.95 for α = 0.05 and α = 0.01) , (3) the students who have high linguistic intelligence, there are differences in the score of the recount text writing skills English language students better use learning techniques (STAD) than the group of students with teaching techniques (CIRC), (Qhit = 7.45> Qtab = 3.15 at level α = 0.05 and α = 0.01). (4) the students who have low linguistic intelligence linguistic, there is a difference in the score of the recount text writing skills English language students better used teaching techniques (CIRC) than the group of students with teaching techniques (STAD), (Qhit = 10.18> Qtab = 3.15 at level α = 0.05 and α = 0.01). Key words: recount text writing skill, learning technique: CIRC and STAD, intelligence linguistic